x^2+y^2=5

x-2y=-3

x=-3+2y

(-3+2y)^2+y^2=5

9-12y+4y^2+y^2=5

5y^2-12y+4=0

D=144-4*5*4=64

sqrtD=sqrt64=8

y1=(12+8)/10=2 x1=-3+2*2=1

y2=(12-8)/10=2/5 x2=-3+2*2/5=-11/5

Then substitute these roots into first equations and check if they are correct.

So, the solution is: x1=1, y1=2; x2=-11/5, y2=2/5

If you have questions feel free to contact me.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up